E-Resources in Academic Libraries: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The internet has spread technological literacy and gave people all over the world fast access to vast resources. E- Resources have proved to be very significant in this world of technology. Hence the readers and the library staff saved time, money and efforts. There is quality in tasks. If e- resources are considered from the point of view of service it, financial issues etc. They are very essential. Because of these e- resources the world scholars can communicate with each other, as well as they can access new groups. Library has catalogue, bibliographical database, and with other academic resources, the paper covenants with the e-resources and their services to academic library movement.